2015
DOI: 10.1115/1.4031226
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Emissions From the Use of Alternative Aviation Fuels

Abstract: Alternative fuels for aviation are now a reality. These fuels not only reduce reliance on conventional petroleum-based fuels as the primary propulsion source, but also offer promise for environmental sustainability. While these alternative fuels meet the aviation fuels standards and their overall properties resemble those of the conventional fuel, they are expected to demonstrate different exhaust emissions characteristics because of the inherent variations in their chemical composition resulting from the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…One particle number mode features a peak at ∼10 nm (nucleation mode) while the second peaks at 40–50 nm (accumulation mode). This particle size distribution has been reported in several other publications. The sulfur content in the fuel has a direct impact on the nucleation particle mode at sufficient distance from the engine exhaust (>15 m) . This is in good agreement with the particle number size distributions in the present measurements (Figure and SI Figure S7–S14) but the impact of the particle mode at 10 nm on the total emitted particle mass is–of course–negligible (Figure B and D).…”
Section: Results and Discussionsupporting
confidence: 92%
“…One particle number mode features a peak at ∼10 nm (nucleation mode) while the second peaks at 40–50 nm (accumulation mode). This particle size distribution has been reported in several other publications. The sulfur content in the fuel has a direct impact on the nucleation particle mode at sufficient distance from the engine exhaust (>15 m) . This is in good agreement with the particle number size distributions in the present measurements (Figure and SI Figure S7–S14) but the impact of the particle mode at 10 nm on the total emitted particle mass is–of course–negligible (Figure B and D).…”
Section: Results and Discussionsupporting
confidence: 92%
“…Published literature is limited for the emissions performance and atmospheric PM evolution of aircraft engines running on sulfur- or aromatic-free jet fuels. ,,, Most other data were collected near the engine exit using a sampling protocol which does not capture the volatile sulfur and organic particles formed in the downstream plume. , , , In addition, some data sets only provide normalized EIs rather than actual emissions, thus further restricting their usefulness for comparison to other work. Table S4 in the Supporting Information shows the emissions reductions associated with the use of the FT jet fuels and blends evaluated in our study as compared to other alternative fuel measurements reported in the literature.…”
Section: Emissions Reduction Discussionmentioning
confidence: 99%
“…These fuels include synthetic paraffinic kerosene (SPK) manufactured by the Fischer–Tropsch (FT) process from coal and natural gas as well as hydroprocessed esters and fatty acids (HEFA) made from various types of biomass and other sources, all of which have similar molecular distributions . Although a number of studies have been conducted on these fuels, limited PM emissions data are available. These studies generally show a decrease in PM mass, number, and size with the use of FT fuel, the magnitude of which depends on engine power, the proportion of alternative fuel used, and the sulfur, aromatics, and napthalene content of the conventional fuel used in the blends. , …”
Section: Introductionmentioning
confidence: 99%
“…Similar to the PMI, fuels containing a higher aromatic content have higher TSI values as these compounds generate more BC during combustion when compared to aliphatic hydrocarbons. The higher emission rates of particles could lead to more coagulation resulting in particles with larger diameters, consistent with the particle number size distributions observed with high fuel aromatic content. One study suggested that operating an engine at the same conditions with fuels containing nearly identical fuel aromatic content but substituting the monoaromatics with naphthalenes (from 0.78% to 1.19% by volume) could increase BC and nonvolatile PM emissions by 40% and 30%, respectively . Multiple NASA studies also suggest that the fuel sulfur and aromatic content affects the volatile PM emissions and contribute to measurement variability.…”
Section: Introductionmentioning
confidence: 59%
“…Early observations showed that different hydrocarbons have different tendencies to generate BC. Many studies often compared petroleum-based jet fuel to renewable jet fuel containing significantly less or even the absence of aromatic hydrocarbons. Observations suggested that low fuel aromatic content, high hydrogen to carbon ratio, and low iso-to-normal paraffin ratio are factors to explain the lowered particulate matter mass (PMM) emissions from aviation turbine engines. Some studies reported that particle size distributions could shift to larger diameter with increasing fuel aromatic content and thus produce higher BC emissions. These studies have implied the possible existence of relationships between BC formation and fuel composition.…”
Section: Introductionmentioning
confidence: 99%